Election of Student Council Chairperson as an Implementation of the Pancasila Student Profile Strengthening Project at Darur Roja Srengat High School Blitar - Mochamad Muchson; Dian Kusumaningtyas; Susi Damayanti; Mohammad Alvian; Elsha Ulfatun Ni’mah (International Journal of Community Service Implementation, 2025)
In the independent curriculum, the Pancasila profile strengthening project is a co-curricular that aims to strengthen student character through the Pancasila student profile. There are six dimensions in the Pancasila student profile, namely faith, devotion to God Almighty and noble character, global diversity, mutual cooperation, creativity, critical reasoning and independence. The project to strengthen the profile of Pancasila learners is collaborative learning across disciplines in observing, exploring, and / or formulating solutions to real issues or problems that are relevant to students. Designed separately from intracurricular and focuses on seeing the process, namely the experience of students while undergoing the process of observation, data collection, processing, execution, evaluation, and reflection. Bringing learning closer to real life, therefore its implementation must be contextualized by taking into account the availability of educational unit resources and students. There are several themes in the project, namely local wisdom, engineering and technology, entrepreneurship, bhinneka tunggal ika, sustainable lifestyle, build the soul of the body, the voice of democracy and employment for SMK. The project of strengthening the profile of Pancasila students starts from mapping dimensions, elements, subelements, themes, titles/topics and time. In the 2024/2025 academic year, SMA Darurroja determined the dimensions of working together, reasoning critically and creatively. The theme of the voice of democracy, the topic/title of the election of the student council chairman, the product of the student council chairman election essay with a time allocation of 162 JP. The results of the project are 7 students developed as expected and 7 students are very developed